Evolution of a paradigm switch in diagnosis and treatment of HPV-driven head and neck cancer: striking the balance between toxicity and cure - Tawk, Bouchra; Debus, Jürgen; Abdollahi, Amir (Frontiers in pharmacology, 2022)
More than a decade after the discovery of p16 immunohistochemistry (IHC) as a surrogate for human papilloma virus (HPV)-driven head and neck squamous cell carcinoma (HNSCC), p16-IHC has become a routinely evaluated biomarker to stratify oropharyngeal squamous cell carcinoma (OPSCC) into a molecularly distinct subtype with favorable clinical prognosis. Clinical trials of treatment de-escalation frequently use combinations of biomarkers (p16-IHC, HPV-RNA in situ hybridization, and amplification of HPV-DNA by PCR) to further improve molecular stratification. Implementation of these methods into clinical routine may be limited in the case of RNA by the low RNA quality of formalin-fixed paraffin-embedded tissue blocks (FFPE) or in the case of DNA by cross contamination with HPV-DNA and false PCR amplification errors. Advanced technological developments such as investigation of tumor mutational landscape (NGS), liquid-biopsies (LBx and cell-free cfDNA), and other blood-based HPV immunity surrogates (antibodies in serum) may provide novel venues to further improve diagnostic uncertainties. Moreover, the value of HPV/p16-IHC outside the oropharynx in HNSCC patients needs to be clarified. With regards to therapy, postoperative (adjuvant) or definitive (primary) radiochemotherapy constitutes cornerstones for curative treatment of HNSCC. Side effects of chemotherapy such as bone-marrow suppression could lead to radiotherapy interruption and may compromise the therapy outcome. Therefore, reduction of chemotherapy or its replacement with targeted anticancer agents holds the promise to further optimize the toxicity profile of systemic treatment. Modern radiotherapy gradually adapts the dose. Higher doses are administered to the visible tumor bulk and positive lymph nodes, while a lower dose is prescribed to locoregional volumes empirically suspected to be invaded by tumor cells. Further attempts for radiotherapy de-escalation may improve acute toxicities, for example, the rates for dysphagia and feeding tube requirement, or ameliorate late toxicities like tissue scars (fibrosis) or dry mouth. The main objective of current de-intensification trials is therefore to reduce acute and/or late treatment-associated toxicity while preserving the favorable clinical outcomes. Deep molecular characterization of HPV-driven HNSCC and radiotherapy interactions with the tumor immune microenvironment may be instructive for the development of next-generation de-escalation strategies.